PERBANDINGAN ABNORMAL RETURN DAN VOLUME PERDAGANGAN SAHAM SEBELUM DAN SESUDAH KEBIJAKAN TAX AMNESTY PERIODE I (Study Kasus Pada Bank Persepsi Penerima Dana Uang Tebusan Tax Amnesty Yang Terdaftar di BEI - Wahyuni Retno Wulandari; Muhamad Agus Sudrajat (INVENTORY: JURNAL AKUNTANSI, 2018)
Mentioned one of the announcements that may affect the price of the securities are governmentrelated announcements, tax amnesty policy is one of the government's policy so it is considered to have an influence on the world of investment in the capital market, therefore this research want to see whether the existence of tax amnesty policy can give abnormal return (AR) and increase volume of stock trading (TVA) on stocks of banks receiving money ransom amnesty tax period I. This research uses event study method. The research data uses secondary data consisting of monthly stock closing price and monthly stock trading volume with 3 months observation period before and 3 months after tax amnesty period I. The market adjusted model is used to calculate the expected return. The hypothesis was tested using paired samples t-test. The samples used are 20 beneficiary taxpayer banks registered on IDX with complete data and normally distributed with one-kolmogorov smirnov test. The results of this study indicate that tax amnesty policy of period I has an effect on abnormal. return and no effect to stock trading volume before and after tax amnesty period I.Keywords: Tax Amnesty, Abnormal Return, Stock Trading Volume